Argatroban and Bivalirudin for Perioperative Anticoagulation in Cardiac Surgery. (February 2018) - Koster, Andreas; Faraoni, David; Levy, Jerrold H.
Abstract : Argatroban and bivalirudin are used as replacement anticoagulants for heparin. The authors review clinical studies for these drugs in the perioperative setting of cardiac surgical patients including extracorporeal management and mechanical support therapy.